(3GdoeYLe GdoeagQSs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s ((3ecI GdoeTQaI s)
(3ChdgG (B:s
(3GdMeO ddg GdPj CfRd GdMOjK s
(3hgh JLQjO CSGfjOg ai GdcJH GdeTghQI hGdLRGA GdefKhQIs
(3ELGRI eTagI YdjgG NW GHf YRe GdePchQ SfI (B858 (3g`s
(3hHgG Jedc ddSjO eQJVi GdRHjOiTGQM GdbGehSs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs